2016
DOI: 10.5812/ircmj.35784
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Parathyroid Adenoma With Radiofrequency Ablation: A Case Report

Abstract: Introduction: The standard treatment for symptomatic primary hyperparathyroidism due to parathyroid adenoma is surgery, but in patients who are not good candidates for surgery, other treatment modalities including ethanol ablation, laser ablation, ultrasound wave ablation, and radiofrequency ablation are used. We describe a patient with multiple medical problems and a parathyroid adenoma who was treated with radiofrequency ablation. Case Presentation: A 47-year-old patient was referred to our hospital (Namazi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The patient had normal serum iPTH and calcium levels at the end of 2-year follow-up. There were no complications in our case, with low complication rates similar to those reported in the literature, 5,[14][15][16][17][18][19][20] suggesting that with appropriate training, this a relatively safe procedure. Operator experience likely plays a role in the complication rate.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The patient had normal serum iPTH and calcium levels at the end of 2-year follow-up. There were no complications in our case, with low complication rates similar to those reported in the literature, 5,[14][15][16][17][18][19][20] suggesting that with appropriate training, this a relatively safe procedure. Operator experience likely plays a role in the complication rate.…”
Section: Discussionsupporting
confidence: 85%
“…Nine reports were identified that described 32 cases of PHPT treated with RFA (Table ). 5,[14][15][16][17][18][19][20][21] In these cases, RFA was performed because of either contraindication to surgery or the patient refusing surgery, and there was limited follow-up. Of note, in 1 case, RFA was performed inadvertently when a parathyroid adenoma was mistaken for a thyroid nodule; this was the only case where there was no improvement in biochemical profile.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the RFA patients either declined to undergo parathyroidectomy (e.g., anxiety or fear of surgical scar) or were deemed poor candidates for surgical management due to their comorbidities ( 12 - 15 , 18 - 20 , 22 , 24 - 27 ). Several comorbidities described included patients with a history of deep vein thrombosis ( 13 ), heart failure ( 22 ), heart disease ( 19 ), brain damage ( 26 ), chronic vascular conditions ( 19 ), and/or acute necrotizing pancreatitis ( 13 ).…”
Section: Discussionmentioning
confidence: 99%